PRINSIP-PRINSIP DASAR EKONOMI ISLAM DALAM BISNIS - Rahmah, Syahidah (Universitas Muhammadiyah Makassar, 2020)
This research aims to look at the concepts of Islamic ethics and basic principles (basic principles) which are based on the values of the Koran which are directed to raise moral values related to the prevention of actions that are not in accordance with the teachings of Islamic law. Using qualitative research methods with data analysis techniques for results and discussion using library research (Library Research) by collecting, reading and browsing a number of books that are used as references. The results show that some of the right concepts to be used in Islamic business ethics to raise moral values according to the teachings of Islamic law are to understand very well the concepts of property and ownership, the concept of wealth distribution, the concept of work and business, and the concept of Halal and Haram